Optimizing Students' Critical Thinking Abilities through the Guided Inquiry Learning Model - Cahyani, Karin; Srigustini, Astri; Sartika, Sri Hardianti (PT FORMOSA CENDEKIA GLOBAL, 2024)
In many schools, students' critical thinking abilities are still relatively low, reflected in their difficulty in analyzing information in depth, constructing logical arguments, and solving problems effectively. This research aims to determine the extent to which applying the Guided Inquiry learning model can improve students' critical thinking abilities. The method used in this research is an experiment with a Nonequivalent Control Group Design. The population used in this research was class XI IPS students at SMAN 6 Tasikmalaya with 198 students, and the sampling technique used was purposive sampling, where the sample was determined based on student activities. Class XI IPS 3 was chosen as the experimental class, which applied the Guided Inquiry model, while class XI IPS 4 was used as the control class, which used the discovery learning model. The instrument used is a set of 22 essay questions. The research results show a significant difference in critical thinking skills between the experimental and control classes, indicating that implementing the Guided Inquiry learning model effectively improves students' critical thinking skills. Hopefully, this research will become a reference for developing more effective strategies and learning models in schools.